Research on an Autonomous Underwater Helicopter with Less Thrusters - Zichen Liu; Jing Zhou; Zhikun Wang; Haifu Zhou; Jie Chen; Xuanshuo Hu; Ying Chen (Journal of Marine Science and Engineering, 2022)
Autonomous underwater helicopter, referred to as AUH, has high maneuverability in the horizontal plane and stable movement in the vertical direction due to its disc shape. Thus, the AUH demonstrates great advantages when working in scenarios that require high accuracy of horizontal movement, fixed height and depth, operation near the seafloor, and so on. In this paper, we propose a new design for an autonomous underwater helicopter with three thrusters in the vertical direction (three-vertical-thrusters), so it is equipped with fewer thrusters while maintaining maneuverability and motion stability. The three-vertical-thruster AUH not only achieves stable attitude control, but also reduces the number of thrusters, enabling the AUH to save space, reduce drag, and decrease power consumption. The three-vertical-thruster structure is designed first and compared with the existing four-vertical-thrusters type to verify its advantages through dynamic analysis and hydrodynamic simulation. The three-vertical-thruster AUH is then modelled, and a compensation method is proposed for its more complex control. The three-vertical-thruster AUH’s controllability and stability are also verified by experiments on the basis of the experimental prototypes.